CLASH: complete lensing analysis of the largest cosmic lens MACS J0717.5+3745 and surrounding structures - Balestra, Italo; Zitrin, Adi; Bartelmann, Matthias (Arxiv, 2013)
The galaxy cluster MACS J0717.5+3745 (z=0.55) is the largest known cosmic lens, with complex internal structures seen in deep X-ray, Sunyaev-Zel'dovich effect and dynamical observations. We perform a combined weak and strong lensing analysis with wide-field BVRi'z' Subaru/Suprime-Cam observations and 16-band Hubble Space Telescope observations taken as part of the Cluster Lensing And Supernova survey with Hubble (CLASH). We find consistent weak distortion and magnification measurements of background galaxies, and combine these signals to construct an optimally estimated radial mass profile of the cluster and its surrounding large-scale structure out to 5 Mpc/h. We find consistency between strong-lensing and weak-lensing in the region where these independent data overlap, <500 kpc/h. The two-dimensional weak-lensing map reveals a clear filamentary structure traced by distinct mass halos. We model the lensing shear field with 9 halos, including the main cluster, corresponding to mass peaks detected above 2.5σ_κ. The total mass of the cluster as determined by the different methods is M_{vir}=(2.8±0.4) × 10^15 M_sun. Although this is the most massive cluster known at z>0.5, in terms of extreme value statistics we conclude that the mass of MACS J0717.5+3745 by itself is not in serious tension with LambdaCDM, representing only a ~2σ departure above the maximum simulated halo mass at this redshift.